Effectiveness of the Sampean Application in Measuring Administrative Management Performance in Cirebon City Government - Febiola Inanta Siswanto; Andeka Rocky Tanaamah; Frids Edward Banunaek (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
SAMPEAN Cirebon is a service portal for managing the administrative needs of Civil Servants (ASN) in the Cirebon City Government. Since its launch, the application has faced several technical issues, mainly because it has never been evaluated from the perspective of end users. This research aims to assess end-user satisfaction, identify areas for improvement, and determine the critical factors influencing user satisfaction with the SAMPEAN Cirebon application. The research applies the End-User Computing Satisfaction (EUCS) method, which consists of five independent variables: content, format, accuracy, ease of use, and timeliness. Data was collected with a voluntary sampling technique, gathering 692 respondents. The data was analyzed using the SEM-PLS method with the SmartPLS application. The results show an R-square value of 0.828, indicating that four variables content, accuracy, ease of use, and timeliness significantly influence ASN satisfaction with the SAMPEAN Cirebon application. In contrast, the format variable yielded a T-statistic of 1.746 and a P-value of 0.081, failing to meet the significance threshold. The practical implications of this study underscore the necessity for the Cirebon City Regional Government to conduct regular evaluations involving direct end-user feedback and to enhance the format aspects of the SAMPEAN Cirebon application.